Perbedaan Deret Konsonan dan Gugus Konsonan Pada Bahasa Indonesia - Lela Nurlaela; Aysilla Afifah; Muhammad Wisnu Nugraha (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research examines the consonant series and consonant clusters of Indonesian. The aim of this research is to determine the difference between consonant series and consonant clusters. The method used in this research is descriptive qualitative. A phoneme series is two different phonemes, which are in different syllables, even though they are located side by side, while a consonant cluster is two different phonemes but which are in a syllable or syllable. Based on the data, there are 52 consonant series, namely: /bd/, /bl/, /bj/, /bs/, /bt/, /dm/, /dj/, /fd/, /fk/, /fs/, /hd /, /hl/, /hk/, /ht/, /kb/, /kd/, /km/, /kn/, /ks/, /kt/, /kw/, /ky/, /lb/, /ld/, /lg/ /lh/, /lk/, /lm/, /ls/, /lt/,/mb/,/md/,/mp/,/mr/,/ms/,/nd/, /rb/, /rc/, /rd/, /rg/, /rh/, /rl/, /rk/, /rm/, /rn/, /rs/, /rt/, /rw/, /ry/ and/sb/. There are 29 consonant clusters, namely: /br/ /bl/, /by/, /dr/, /dw/, /dy/, /fl/, /fr/, /gl/, /gr /, /kl/, /kr, /ks, /kw/, /pr/, /pl/, /ps/, /sl/, /sp/, /sr/, /st/, /sw/, /sk /, /sy/, /tr/, /ty/, /spr/, /str/, /and /skr/.